Characterization of a novel micro-pressure double-cycle reactor for low temperature municipal wastewater treatment. Issue 3 (28th January 2023) - Ai, Shengshu; Du, Linzhu; Nie, Zebing; Liu, Wenai; Kang, Hua; Wang, Fan; Bian, Dejun
ABSTRACT: To solve the deterioration of effluent caused by low temperature in urban sewage treatment plant in cold areas, a new type of reactor was proposed, the biochemical environmental and low-temperature operating characteristics of the reactor were studied. Through analysis of flow simulation and dissolved oxygen (DO) distribution when the aeration rate was 0.6 m 3 /h, it showed that there were many different DO environments in the reactor at the same time, which provided favourable conditions for various biochemical reactions. The operation test showed that the average effluent removal rate of COD, TN, NH4 + -N and TP was 92.53%, 74.57%, 89.61% and 96.04%, respectively. And there were a variety of functional bacteria related to nitrogen and phosphorus removal in the system, most of them with strong adaptability at low temperatures. Among the dominant microorganisms, Flavobacterium and Rhodobacter were related to denitrification, Aeromonas and Thiothrix were related to phosphorous removal. Denitrifying phosphorus removal was the main way of phosphorus removal. Picrust2 results showed that the reactor operated well at low temperature, and the regional difference distribution of nitrification genes further confirmed the existence of functional zones in the reactor. The results showed that the Micro-pressure Double-cycle reactor worked well at low temperature, which provided a new idea and way for the upgrading of urban sewage treatment plants in cold areas. GRAPHICAL ABSTRACT: UF0001